Physiological and transcriptomic responses to starvation in the corallivorous crown-of-thorn starfish - Yang, Litong; Zhang, Ying; Chen, Huizhen; Gao, Qian; Luo, Peng; Hu, Jianxing; Zheng, Fanyu; Yuan, Yunyu; Fu, Liang; Chen, Chang (Frontiers in Marine Science, 2022)
The outbreak of coral-eating Acanthaster spp., commonly known as the Crown-of-Thorn Starfish (CoTS), contributes to a significant proportion of coral loss in the tropical Indo-Pacific region. After the dramatic loss of coral due to their predation, CoTS is expected to face food shortages before coral recovers, which is usually accompanied by the sudden disappearance of its population. To reveal the response of CoTS to starvation stress, we conducted a four-month starvation experiment to investigate the physiological and molecular changes in the stomach tissue by combining the metabolites and enzyme activity measurements with transcriptome analysis. The results showed that the concentrations of primary metabolites and associated enzyme activities, as well as the amount of total antioxidant were not significantly altered between fed and starved CoTS in any case. However, starvation suppressed the expression of the genes involved in glycolysis and citrate cycle, development and movement, but enhanced that of the genes associated with sleep promotion, immunity, lysosome and glucose supply. This suggests that long-term starvation may induce CoTS to enter into a dormancy-like status characterized by reduced unnecessary physical activities for survival, accelerated recycling of nutrients, and enhanced immunity.